Analisis Minat Petani Muda Dalam Berwirausaha Pada Bidang Pertanian Tanaman Kopi di Desa Osango, Kabupaten Mamasa - Tuti Supatminingsih; Thamrin Tahir (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
Youth participation in agriculture is decreasing from year to year. Agriculture was considered unprofitable, unclean, and stupid. The lack of enthusiasm of young people in agriculture will have an impact on the sustainability of agriculture. The pattern of agricultural entrepreneurship is considered capable of increasing farmers' income, which in turn stimulates the attention of young farmers in the agricultural sector. Furthermore, agricultural entrepreneurship is seen as able to provide a new view that agriculture does not have to be old-fashioned, unclean, or illiterate. The purpose of this study was to determine the interest of young farmers in coffee cultivation. The research method used is descriptive, using a qualitative approach. The research data includes primary and secondary sources. Focus Group Discussion and Key Informant Interview approaches were used to obtain data. The key informants in this study were young farmers aged between 18 and 40 years who had their own coffee plantations, came from farming families, and processed their own coffee. Three steps of data analysis were used: data condensation, data presentation, and verification/drawing conclusions. According to the findings of this survey, young farmers between the ages of 19 and 40 are interested in starting their own coffee plantations. This interest stems from the possibility of increasing income through processed coffee. In addition to increasing income, the prestige of being a coffee farmer and processor provides a fresh perspective and pride for young farmers. Access to capital is felt to be lacking because land ownership is still controlled by the family, as well as a lack of discipline and character as an entrepreneur, are some of the challenges faced by young farmers in doing business